A potential link between the structure of iron catalysts and Fenton-like performance: from fundamental understanding to engineering design. Issue 24 (7th June 2022) - Li, Ling; Yin, Zhuo; Cheng, Min; Qin, Lei; Liu, Shiyu; Yi, Huan; Zhang, Mingming; Fu, Yukui; Yang, Lu; Tang, Chensi; Zhou, Xuerong; Xu, Fuhang; et al.
Abstract : Modulating the structure of Fe catalysts is possible to alter the exposure of active sites, electron density around active sites, coordination number, charge transfer or mass transfer limitation, and thus affect Fenton-like catalytic activity. Abstract : A heterogeneous Fenton-like process on the basis of Fe catalysts has been widely studied for wastewater treatment, which overcomes the problem of the pH limitation and sludge production in homogeneous Fenton systems. Nevertheless, excessive H2 O2 is typically required to reach a desirable Fenton-like efficiency of Fe catalysts, challenging their environmentally sustainable application. Hence, numerous research studies have been carried out to improve the utilization efficiency of Fe catalysts for H2 O2 . Among various strategies, structural design is possible to endow Fe catalysts with novel physiochemical properties, such as different coordination environments, more active sites and enhanced charge transfer, which has attracted wide interest with tremendous research progress being made. In this review, we mainly focus on the recent advances in designing "smart" Fe catalysts for efficient Fenton-like reactions through structural design. The influence mechanisms of some structural properties ( i.e., exposed facet, defects, catalyst size, and space confinement) on the Fenton-like activity of Fe catalysts are carefully discussed to generalize structure–activity relationships. Afterward, we will briefly summarize the characterization techniques for examining these structural properties, followed by strategies to prepare Fe catalysts with a specific structure. This review intends to offer valuable information for designing and fabricating efficient environmental catalysts for a heterogeneous Fenton-like reaction.